SELÇUKLU DÖNEMİ`NDE HALEP - KIRKIL, EMİN (Fırat Üniveristesi, 1999)
The stury in which Arabic vakayinames were used is based on some Alepin muallifs such as Ibn al Adim, Ibn al Şaddad and Ibn al Chihna. After Malik-Shah state of war (attact) to North Syria Aleppo was connekted to Seljuk Empire. Aleppo's first governnor Kasim al Dawla Aq-Sounqur. After this period Aleppo's social condition, physical planning and economic life started to change into the top level in the time of Nur al-Din Mahmud Zangi. Theretore in that period Aleppo got a new style and became a part of Turkish cultural geography. Due to this event, in the later periods Turkish donination was accapted easily. KEY WORDS: Aleppo ( Halep), Kasim al Dawla Aq-Sounqur (Kasimuddevle Aksungur), Nur al-Din ( Nurettin), North Syria ( Kuzey Suriye).

it. SUMMARY Phd Thesis Emin KIRKIL This study researchess the city structure Aleppo and contains the period between 1086 and 1 183. The stury in which Arabic vakayinames were used is based on some Alepin muallifs such as Ibn al Adim, Ibn al Şaddad and Ibn al Chihna. After Malik-Shah state of war (attact) to North Syria Aleppo was connekted to Seljuk Empire. Aleppo's first governnor Kasim al Dawla Aq-Sounqur. After this period Aleppo's social condition, physical planning and economic life started to change into the top level in the time of Nur al-Din Mahmud Zangi. Theretore in that period Aleppo got a new style and became a part of Turkish cultural geography. Due to this event, in the later periods Turkish donination was accapted easily. KEY WORDS: Aleppo ( Halep), Kasim al Dawla Aq-Sounqur (Kasimuddevle Aksungur), Nur al-Din ( Nurettin), North Syria ( Kuzey Suriye).
Keywords: Tarih; History